Data Transfer between Cloud Document Management Systems in Serverless Paradigm - Bhole, Ritika; Dalvi, Sanket; Acharya, Manas; Nirkhe, Sahil; Rane, Pradnya; Jain, Sheetal (2021 4th International Conference on Computing and Communications Technologies (ICCCT), 2021)
Data and communication are at the heart of business and interactions. With the onset of economic and reliable Document Management System (DMS) providers, there has been a large-scale migration to these cloud-based services. When it comes to Data Transfer we find ourselves in the realm of mailing files, link sharing, FTP and the list goes on, however, all of these methods involve some level of local computing and storage resource consumption and do not support transfers across different DMS providers. This paper proposes a system that aims to facilitate cloud-agnostic data transfers built over a cloud system with Serverless computing paradigm.